MEMPERTAHANKAN COMPETITIVE ADVANTAGE PADA PERUSAHAAN SEKTOR INDUSTRI NON-CYCLICAL MELALUI ANALISIS SWOT - Suripto Suripto; Wahyudi Widodo; Immami Immami (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
Company Performance is a description of the company's achievements in its operational activities either from financial, marketing, fund raising, technological development, human resource quality, or social and environmental aspects. As an effort to output good performance, management needs to think about several strategies and synergize them with the company's current environmental situation and conditions. SWOT analysis is a widely known internal and external environmental analysis instrument. This analysis is based on the assumption that an effective strategy will minimize weaknesses and threats. This research aims to present a review and analysis of competitive advantage in non-cyclical companies using the SWOT analysis technique. From this research, it can be concluded that the use of SWOT analysis in the business world offers many benefits, not only in the macro scope, but can also be used to analyze the company's internal strengths, weaknesses, opportunities and threats in the micro scope. This analysis is useful as a form of evaluation and monitoring of achievements of business activities as well as for designing strategic plans and operational strategies to improve company performance. Keywords: Company Performance, SWOT Analysis, Strategic Planning, Non-cyclical Companies